2019
DOI: 10.1007/s00403-019-01890-4
|View full text |Cite|
|
Sign up to set email alerts
|

Atopic dermatitis and autoimmunity: the occurrence of autoantibodies and their association with disease severity

Abstract: Atopic dermatitis (AD) is a widespread condition that appears to be increasing in prevalence and severity worldwide, yet the underlying mechanisms are not well understood. Recent research has identified various similarities between AD and autoimmune conditions, as well as indicating that there may be an association between AD and autoimmunity. This systematic review evaluates the association between AD and autoimmunity, as well as between severity of disease in AD and autoimmunity, with an emphasis on the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 56 publications
4
29
0
3
Order By: Relevance
“…Taken together, rAsp f 6 recognition possibly represents the signature of an autoimmune process against human MnSOD, occurring in at least a subset of patients affected by AD . The presence of autoantibodies of the IgE class and its association with disease severity has been suggested . In accordance with Mittermann et al, we also found a significantly higher frequency of IgE reactivity to Malassezia sympodialis rMala s 11 in severe AD, as a further confirmation of the presence of MnSOD reactivity in AD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, rAsp f 6 recognition possibly represents the signature of an autoimmune process against human MnSOD, occurring in at least a subset of patients affected by AD . The presence of autoantibodies of the IgE class and its association with disease severity has been suggested . In accordance with Mittermann et al, we also found a significantly higher frequency of IgE reactivity to Malassezia sympodialis rMala s 11 in severe AD, as a further confirmation of the presence of MnSOD reactivity in AD.…”
Section: Discussionsupporting
confidence: 91%
“…30 The presence of autoantibodies of the IgE class and its association with disease severity has been suggested. 31 In accordance with Mittermann et al, 32 we also found a significantly higher frequency of IgE reactivity to Malassezia sympodialis rMala s 11 in severe AD, as a further confirmation of the presence of MnSOD reactivity in AD.…”
Section: (B)supporting
confidence: 91%
“…In more recent years, a wide range of autoantigens have been described. The most relevant targets are summarized in Table 2 and were previously listed by others [ 21 , 22 , 56 ]. Patients with the highest total serum IgE values, showed the highest frequency of anti-keratinocyte IgE [ 33 ].…”
Section: Ige Autoreactivity In Atopic Dermatitismentioning
confidence: 99%
“…AD shows a strong genetic predisposition associated with epidermal barrier dysfunction and type 2 immune responses. The severity of the disease has been associated with allergen sensitization and IgE levels as well as with the prevalence of autoreactive IgE [ 1 , 2 , 3 , 4 , 5 ]. Dupilumab, which is a monoclonal antibody targeting the IL-4Rα chain, is approved to treat moderate to severe symptoms in children from six years old to adults, and is currently evaluated in toddlers from six months to five years old.…”
Section: Atopic Dermatitis: a Multifactorial Pathogenesismentioning
confidence: 99%
“…It is thought to be an essential part of its pathogenesis or of its chronification [ 28 , 40 ]. Two independent systematic reviews summed-up the relationship between AD, its severity, and autoreactive antibodies [ 4 , 5 ]. Autoreactive IgG with various specificities have been detected in multiple studies.…”
Section: Atopic Dermatitis: a Multifactorial Pathogenesismentioning
confidence: 99%